Massive Uterine Leiomyoma in a Patient with Friedreich's Ataxia: Is There a Possible Association? - Evangelos P. Misiakos; Elli Siama; Dimitrios Schizas; Constantinos Petropoulos; Nikos Zavras; Nikos Economopoulos; Alexandros Charalabopoulos; Anastasios Macheras (Case Reports in Medicine)
A possible association between Friedreich's ataxia (FA) and neoplastic development has been recognized. FA patients have low frataxin levels and insufficient response to oxidative stress. In these patients fibroblasts are characterized by a high rate of mutations. Herein, a case of a 39-year-old woman with FA tetraplegia, who was admitted in our department with intestinal obstruction due to a huge uterine tumor, is described. An abdominal CT revealed a huge intra-abdominal mass originating from the right cornu of the uterus. Tumor excision and adhesionlysis were performed. The histological examination of the tumor revealed a leiomyoma. FA patients seem to present with a variety of neoplasms uncommon for their young age. This is the first report of a leiomyoma originating from the genital system in a female patient with FA tetraplegia. Therefore it is important to identify neoplasms at an early stage in patients with FA and start immediate therapy.